The Poetics of Spontaneous Order:: Austrian Economics and Literary Criticism - Part 1 - Cantor, Paul A. (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2014)
The author criticizes the standardization of the economic critique of the literature. It draws attention to the anticapitalist spirit of economic discussions in literature, often reproducing an openly pro-socialism speech. He questions if this way of thinking would be the most useful in the analysis of literature Cantor argues that the most effective way to counteract the negative effects of the Marxist literary criticism is not to deny that the economy has relevance for literature, but offering a positive alternative to Marxism to the relationship between literature and economics, as the Austrian School of Economics ideas.